If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75(4y + 2) = 4.5 Reorder the terms: 0.75(2 + 4y) = 4.5 (2 * 0.75 + 4y * 0.75) = 4.5 (1.5 + 3y) = 4.5 Solving 1.5 + 3y = 4.5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + 3y = 4.5 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + 3y = 4.5 + -1.5 3y = 4.5 + -1.5 Combine like terms: 4.5 + -1.5 = 3 3y = 3 Divide each side by '3'. y = 1 Simplifying y = 1
| 5/6/8/1 | | 3(x-3)+2(x+5)=21 | | 7-3x=-23 | | x(2x-5)(x+6)= | | 2/3x=-7 | | 5/6/8 | | n/9-4=11 | | 125x+3=52x+4 | | 0.4p-2=0.8p-3 | | 8x+2(x-9)=82 | | -7x=-4 | | 93x=27 | | 0=5.1x+0.3x | | 8x+12(x-9)=82 | | 1x^2-3x-12=0 | | -16t^2+288t-512=0 | | 12-2x=12+2x | | x^4=4x | | 2x+1+3(x-6)=23 | | 2x+6=69+-5x | | 0.5(3x-5)=8 | | 6(x-1)=3(x-2) | | 2/-4/3=x | | 2/-4/3 | | 5+7(x+1)=12+10x | | x+3/4=17/18 | | 2(x+2)=1x-5 | | -10-9y=-13 | | 4/6x-2/6 | | 8/9*4/5 | | 7x-12x=-45+15 | | 4(y-3)-2y=5(3y+1) |